Influence of Political Connections and Efficiency on Financial Performance and Its Implications on Firm Value - Hazim, Raihan; Mediawati , Elis (Journal of Developing Economies, 2023)
This research aims to determine the influence of political connections and efficiency on financial performance and their implications for stock value. The research design employed in this study is quantitative research. The population of this study consists of 66 companies in the mining sector listed on the IDX Sector Energy. The sampling technique used in this research is purposive sampling. The data used are secondary data obtained from www.idx.co.id. Hypothesis testing is conducted using Partial Least Square analysis. The results of this study indicate that 1) Political connections have a non-significant positive influence on financial performance; 2) Efficiency has a significant favorable influence on financial performance; 3) Financial performance has a significant favorable influence on company value; 4) Financial performance has a non-significant positive mediating effect on the relationship between political connections and company value; 5) Financial performance has a significant positive mediating effect on the relationship between efficiency and company value.